THE CUSTOMARY PHENOMENON OF SUMBANGSIH IN MUSIRAWAS URBAN MUSLIMS BASED ON ISLAMIC LAW - Nurmala Nurmala; Resti Aningsih; Musda Asmara; Hina Al Kindiya (Akademika : Jurnal Pemikiran Islam, 2023)
This study comprehensively described the customary phenomenon of Sumbangsih on Musirawas urban Muslims. It has become a custom in Musirawas if a wedding party has to be held with great fanfare and hires a single organist. The Musirawas community does not need to bother with the cost of the party because the surrounding community is assisted through the Sumbangsih custom, but this custom has several negative impacts, so further studies are still needed. The customary phenomenon of Sumbangsih will be analyzed using ushuliyah studies using ‘urf theory. This field research uses interview data collection techniques, observation, and documentation. The approach used in this study is sociological normative. While the data analysis technique was carried out in three stages: data reduction, data presentation, and conclusion. An important finding in this study is that custom Sumbangsih are assistance or support in the form of money given when someone is having a wedding. The system for carrying out this donation event is based on a nominal level starting from the largest to the smallest. People who donate will go up on stage when there is a direction from the presenter and will line up from those who donate the most to the smallest the donation will be recorded, and the nominal will be stated. The second finding, the Sumbangsih (donation) custom belongs to al-'urf al-fasidah because if this Sumbangsih is carried out, it causes a lot of harm or immorality, such as the many illegal singers dressed in sexy clothes looking for saweran (giving money), gambling, drunkenness, and fights. So, it is necessary to harmonize Islamic teachings in this custom Sumbangsih by removing the mudhorat or immorality that appears in this custom.